"UNIVERSITY OF THE THIRD AGE" AS A FORM OF SENIOR CITIZENS’ LIFELONG EDUCATION - Lezhnina, Larisa; Morova, Natalia; Domracheva, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article is devoted to the urgent problem of finding ways of social integration of senior citizens  to the conditions of the rapidly changing society. The main idea is to use the resources of life-long education for providing retired people  with the conditions to obtain information about the world on a systematic basis. The subject of the research are the form and the content of senior citizens’ lifelong education that is aimed at preserving their active life style and enriching their intrapersonal potential. The article gives the social-pedagogical model of lifelong uducation of elderly people that corresponds to their needs, and describes  the author's conceptual basis (openness of education, voluntariness, focus on the learners’ needs) and the content of the model (giving knowledge, developing skills, interaction and self-development training). The methods of the research are modeling and pedagogical natural experiment. The five-year experience of implementing the model of senior citizens’ lifelong education in the form of  "University of the Third Age" allows the authors to conclude that it is effective. In the students’ opinion, the educational programs of "University of the Third Age" meet their cognitive needs, provide their social integration, help them to maintain active life style, increase their satisfaction with the quality of their life. Thus, higher educational institutions can and should become the place where senior citizens can get education and training.